Long-Term Benefits of Continuous Glucose Monitoring Combined with Insulin Pump Therapy - Zulfiqar, Rukhsana; Abbas, Komal; Khan, Saeeda; Fatima, Kanwal; Manzoor, Adnan; Muhammad Awais (Indus Journal of Bioscience Research, 2024)
Objective: To evaluate the long-term efficacy and safety of continuous glucose monitoring (CGM) combined with insulin pump therapy, focusing on glycemic control, patient adherence, quality of life, and reduction in diabetes-related complications. Methodology: A prospective cohort study was conducted on 100 patients with type 1 or insulin-dependent type 2 diabetes from February 2023 to July 2024 at a Tertiary Care Hospital in Karachi. Participants, aged 18–75 years, used CGM-integrated insulin pump therapy. Key metrics included HbA1c levels, time-in-range (TIR), adherence rates, and quality-of-life scores assessed at baseline and study completion. Statistical analyses were performed using SPSS, with significance set at p < 0.05. Results: The mean HbA1c level decreased to 8.14% (SD: 0.83, p = 0.003), while TIR improved to 67.90% (SD: 12.57, p = 0.001). Adherence rates were high, averaging 89.81% (SD: 5.62, p = 0.02), reflecting strong patient engagement. Quality-of-life scores also increased significantly, with a mean score of 79.74 (SD: 11.28, p = 0.015). No severe adverse events were reported, underscoring the safety of the intervention. Conclusion: CGM combined with insulin pump therapy significantly improves long-term glycemic control, adherence, and quality of life in diabetes management. These findings highlight the clinical and psychosocial benefits of integrating these technologies, particularly in achieving sustainable outcomes. Future research should explore broader population impacts, cost-effectiveness, and advanced technological integration